Trends of inequalities in care seeking behavior for under-five children with suspected pneumonia in Ethiopia: evidence from Ethiopia demographic and health surveys (2005-2016) - Gebretsadik Shibre; Betregiorgis Zegeye; Dina Idriss-Wheeler; Sanni Yaya (BMC, 2021)
Abstract Background Pneumonia is a leading public health problem in under-five children worldwide and particularly in Africa. Unfortunately, progress in reducing pneumonia related mortality has been slow. The number of children with symptoms of pneumonia taken to health facilities for treatment is low in Ethiopia, and disparities among sub-groups regarding health seeking behavior for pneumonia have not been well explored in the region. This study assessed the trends of inequalities in care seeking behavior for children under five years of age with suspected pneumonia in Ethiopia. Methods Using cross-sectional data from the 2005, 2011 and 2016 Ethiopia Demographic and Health Surveys (DHS) and the World Health Organization's (WHO) Health Equity Assessment Toolkit (HEAT), this study investigated the inequalities in health seeking behavior for children with suspected pneumonia. Four measures of inequality were calculated: Difference, Ratio, Slope Index of Inequality and Relative Index of Inequality. Results were disaggregated by wealth, education, residence, and sex with computed 95% Uncertainty Intervals for each point estimate to determine significance. Results The percentage of under-five children with symptoms of pneumonia who were taken to a health facility was significantly lower for children in the poorest families, 15.48% (95% UI; 9.77, 23.64) as compared to children in the richest families, 61.72% (95% UI; 45.06, 76.02) in 2011. Substantial absolute (SII = 35.61; 95% UI: 25.31, 45.92) and relative (RII = 4.04%; 95% UI: 2.25, 5.84) economic inequalities were also observed. Both educational and geographic inequalities were observed; (RII = 2.07; 95% UI: 1.08, 3.06) and (D = 28.26; 95% UI: 7.14, 49.37), respectively. Economic inequality decreased from 2011 to 2016. There was no statistically significant difference between male and female under-five children with pneumonia symptoms taken to health facility, in all the studied years. Conclusions Health care seeking behavior for children with pneumonia was lower among the poorest and non-educated families as well as children in rural regions. Policies and strategies need to target subpopulations lagging behind in seeking care for pneumonia treatment as it impedes achievement of key UN sustainable development goals (SDGs).